INCLUSIVE LANGUAGE EDUCATION IN CONTEMPORARY PEDAGOGY: THEORETICAL FOUNDATIONS AND PRACTICAL IMPLEMENTATION - BAZAROV, Zokir (The Lingua Spectrum, 2025)
This article examines the theoretical foundations, pedagogical implications, and practical challenges of inclusive language education in modern multilingual learning environments. Drawing on contemporary sociolinguistic, cognitive, and pedagogical frameworks, the paper explores how inclusive approaches support equity, accessibility, and meaningful participation for learners with diverse linguistic, cultural, and cognitive backgrounds. Special attention is given to differentiated instruction, multilingual pedagogies, Universal Design for Learning (UDL), and sociocultural models that position learner diversity as a resource. The study emphasizes that inclusive education is not merely a methodological set of tools, but a comprehensive educational philosophy grounded in human dignity, linguistic justice, and equitable access.